2018
DOI: 10.1007/s00425-018-2929-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-ketoglutarate dehydrogenase activity affects adventitious root growth in poplar via changes in GABA shunt

Abstract: Blocking α-ketoglutarate dehydrogenase results in up-regulation of γ-aminobutyric acid (GABA) shunt activity, and inhibits the growth of poplar adventitious roots (ARs), indicating that AR growth is closely associated with GABA shunt. γ-Aminobutyric acid (GABA) shunt starts from α-ketoglutarate in the tricarboxylic acid cycle, which is thought to represent the cross road between carbon and nitrogen metabolism. Previous studies (Araújo et al. 2012b, Plant Cell 24: 2328-2351) have shown that blocking α-ketogluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“… 50 Similarly, a high GABA content also inhibits adventitious root growth. For example, adventitious root growth of poplar is inhibited if the GABA level is increased in poplar lines by inhibition of α-ketoglutarate dehydrogenase activity , 51 overexpression of PagGAD2 52 or exogenous GABA application. 51 , 52 The changes in GABA shunt activity affect cell-wall carbon metabolism-related genes and phytohormone (IAA, ABA, and ethylene) signaling.…”
Section: Gaba Acts As a Signal Molecule In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 Similarly, a high GABA content also inhibits adventitious root growth. For example, adventitious root growth of poplar is inhibited if the GABA level is increased in poplar lines by inhibition of α-ketoglutarate dehydrogenase activity , 51 overexpression of PagGAD2 52 or exogenous GABA application. 51 , 52 The changes in GABA shunt activity affect cell-wall carbon metabolism-related genes and phytohormone (IAA, ABA, and ethylene) signaling.…”
Section: Gaba Acts As a Signal Molecule In Plantsmentioning
confidence: 99%
“… 51 , 52 The changes in GABA shunt activity affect cell-wall carbon metabolism-related genes and phytohormone (IAA, ABA, and ethylene) signaling. 51 , 52 …”
Section: Gaba Acts As a Signal Molecule In Plantsmentioning
confidence: 99%
“…Similarly, exogenous GABA inhibits primary root growth in Arabidopsis (Renault et al 2011). Recently, it was reported that the inhibition of AR growth by blocking α-ketoglutarate dehydrogenase (α-KGDH) was accompanied by changes in GABA shunt (Yue et al 2018). In poplar (Populus alba × P. glandulosa), endogenous GABA accumulation not only inhibited the AR growth, but also delayed AR primordia formation and the AR appearance within one day.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of GABA content in the wild-type and mutant seedlings was modified from previously reported methods ( Liu et al, 2018 ; Yue et al, 2018 ). Briefly, 0.1 g of the wild-type lap2-3 and cat2-1 mutant seedlings were ground with liquid nitrogen to a fine powder and extracted using 1 ml acetonitrile.…”
Section: Methodsmentioning
confidence: 99%